Student Challenges in Understanding Newton's Law: An Analysis Using Isomorphic Multiple Choice Items - Rahayu, Putri; Kusairi, Sentot; Khusaini, Khusaini (Jurnal Pembelajaran Fisika, 2024)
Newton's Law is a basic concept in physics learning at the high school and college levels, but students' conceptual understanding of the concept is still weak.  This study aims to analyze students' difficulties in the concept of Newton's Law by looking at the consistency of students' answers to isomorphic problems. The research method used quantitative research by means of a survey. The respondents were 118 students (58 high school students and 60 MAN students) who had taken the Newton's Law chapter.  The research instruments were adapted from the Force Concept Inventory (FCI) and isomorphic multiple-choice question (IMCI) which were validated by two physics experts. The analysis technique uses isomorphic analysis by looking at the consistency of student answers to the concept of Newton's Law.  Based on the consistency of the answers, three groups of students’ conceptual understanding were determined, namely the “Understanding” when students were consistently correct on three isomorphic items, “Moderately Understanding” if they were consistently correct on two isomorphic items, and “Not Understanding” if only one answer was correct or did not answer correctly on the isomorphic items. The study found that students' conceptual understanding on all isomorphic items was low. especially in Theme 5 which is about the concept of analyzing the relationship between force and the speed of motion of objects with 97.46% of students having difficulties, and Theme 3 with the concept of action-reaction on Newton's Third Law with 95.76% having difficulties. The recommendation for further research is to apply learning methods to overcome students' difficulties in Newton's LawKeywords: Conceptual understanding, newton’s law, Isomorphic question.DOI: http://dx.doi.org/10.23960/jpf.v12.n2.202402